EFEKTIVITAS KEBIJAKAN PERATURAN MENTERI PERHUBUNGAN NOMOR 134 TAHUN 2015 TENTANG PENYELENGGARAAN PENIMBANGAN KENDARAAN BERMOTOR DI JALAN (STUDI KASUS JEMBATAN TIMBANG BALAI RAJA) - Safendra, Sandy; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
One of the objectives of the government, namely national development as a form of Pancasila experience. Especially in vehicles transporting goods in traffic and road transportation. However, the problem of excessive transportation of goods causes problems with the facilities and infrastructure of road safety and road conditions, as in the contents of Law No. 22 of 2009 concerning Traffic and Road Transportation. Goods transported by the Minister of Transportation number 134 of 2015 concerning the implementation of the handling of motorized vehicles that violate the rules is a problem that is always encountered in many regions throughout Indonesia, and the problem always recurs and seems difficult to overcome completely. This study uses Willian N Dunn's theory which states that the effectiveness of policies there are several indicators as follows, namely Efficiency, Adequacy, Grading, Responsiveness, and Decision. Data analysis used is a qualitative descriptive method. Data sources consist of primary data and secondary data through observation, interview and documentation techniques conducted at the Balai Raja motor vehicle weighing unit. Data analysis techniques using triangulation techniques. The results of the study show that there are several factors that influence the effectiveness of the policy of implementing motor vehicle weighing implementers, namely the lack of personnel or human resources (HR). In addition, there is a lack of awareness of truck drivers in transportation and the procedures for cargo transportation. Therefore, it is important to carry out the weighing of motorized vehicles to maintain road infrastructure, order and security in the use of roads.Keywords: Effectiveness of Public Policy Policy, Goods Transport Cost.